Magnetic-Field Immunity Examination and Evaluation of Transcutaneous Energy-Transmission System for a Totally Implantable Artificial Heart. (9th January 2012) - Yamamoto Yamamoto, Takahiko Takahiko; Koshiji Koshiji, Kohji Kohji
Abstract : Transcutaneous energy transmission (TET) is the most promising noninvasive method for supplying driving energy to a totally implantable artificial heart. Induction-heating (IH) cookers generate a magnetic flux, and if a cooker is operated near a transcutaneous transformer, the magnetic flux generated will link with its external and internal coils. This will affect the performance of the TET and the artificial heart system. In this paper, we present the design and development of a coil to be used for a magnetic immunity test, and we detail the investigation of the magnetic immunity of a transcutaneous transformer. The experimental coil, with five turns like a solenoid, was able to generate a uniform magnetic field in the necessary bandwidth. A magnetic-field immunity examination of the TET system was performed using this coil, and the system was confirmed to have sufficient immunity to the magnetic field generated as a result of the conventional operation of induction-heating cooker.